PROBLEMATIKA TAFSÃ®R BI AL-RAâ€™Y DALAM LINTAS MAZHAB DAN GENERASI - Achmad, Danial (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2013)
Attempts to interpret the Koran according to God?s will done many Muslim scholars in order to make the Koran as a guide to life. Diverse products that leave the interpretation of the rationale, methods and background exegetes in different ranges of time and place are emerging in all generations. The diversity of interpretations of this product is reasonable conditions on the way the dynamics of history. Al-Tabarî, ?Abduh, al-Zamakhsharî, and al-Tabâtabâ?î is most commentators who have given a big hand in developing the methodology of interpretation and unravel the meanings contained in the Koran. Similarly, the Shahrûr, although it only partially interpret the Koran as interpreted thematic (mawdû?î). Therefore, an important step to be taken is the objectivity of studies related ittijâh, manhaj, and results interpretation to then be selected and distinctions, in order to know whether that interest is already making an interpretation of the purpose of an examination rulings or rulings which is allowed, such as ijtihâd of the Prophet, his companions, tâbi?în, or imams schools.